Connection on Events of Subclause to Main Clause: Analyzing Sentence Construction in Kyoukasho (Japanese Textbooks) - Roni, Roni; Nurhadi, Didik; Martiana, Twin D (Makassar State University, 2023)
Abstract. Along with the rising influence of Japanese in many spheres of life, many language learners around the world have learned Japanese. Kyoukasho, which means